1993
DOI: 10.1080/01140671.1993.9513767
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit pollination: An unbiased estimate of wind and bee contribution

Abstract: The role of wind and bees in kiwifruit (Actinidia deliciosa (A. Chev.) C.F. Liang et A.R. Ferguson) pollination was investigated using large cages enclosing 80 mature vines and assembled so as to prevent insects entering without reducing wind flow within the cages. Monitoring wind speed within the cage and in the open orchard showed that the cages were suitable for such experimentation. Cages without hives, cages with hives, open pollination with hives, and hand pollination were compared during 1990 and 1991. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 13 publications
4
48
0
Order By: Relevance
“…By caging a male and female vine together, Testolin et al (1991) reported 69% fruit set and a mean fruit weight of 58 g as a result of wind pollination compared with an open (uncaged) honey bee pollinated control of 98% fruit set and a mean fruit weight of 88 g. This represented a total yield reduction of up 50% in the absence of bees. Costa et al (1993) using much larger cages reported that hand pollination resulted in bigger fruit (119 g) than did bee supplementation (78 g), caging with bees (90 g), and wind pollination (66 g). Vaissiere et al (1996) used paired flowers instead of cages and reported that honey bees disperse pollen in the air while foraging on kiwifruit flowers, thus contributing to passive pollination in kiwifruit.…”
Section: Effect On Fruit Set and Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…By caging a male and female vine together, Testolin et al (1991) reported 69% fruit set and a mean fruit weight of 58 g as a result of wind pollination compared with an open (uncaged) honey bee pollinated control of 98% fruit set and a mean fruit weight of 88 g. This represented a total yield reduction of up 50% in the absence of bees. Costa et al (1993) using much larger cages reported that hand pollination resulted in bigger fruit (119 g) than did bee supplementation (78 g), caging with bees (90 g), and wind pollination (66 g). Vaissiere et al (1996) used paired flowers instead of cages and reported that honey bees disperse pollen in the air while foraging on kiwifruit flowers, thus contributing to passive pollination in kiwifruit.…”
Section: Effect On Fruit Set and Yieldmentioning
confidence: 99%
“…The relative importance of honey bees and wind in kiwifruit pollination is not clear. Although honey bees appear to be responsible for most kiwifruit pollination, wind may also be an important vector (Palmer-Jones & Clinch 1974;Hopping 1979;Jay & Jay 1984;Testolin et al 1991;Costa et al 1993;Vaissiere et al 1996). Literature from New Zealand, United States, Spain, and France indicate that honey bees are essential for pollination and the production of large fruit (Palmer-Jones & Clinch 1974;McKay 1976;Clinch 1984;Ponchia & Youssef 1991;Vaissiere et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Vanneste et al 2013). Kiwifruit flowers are predominantly insect pollinated (Goodwin et al 2013), and honey bees are important for obtaining consistent fruit set and size (Craig et al 1988;Costa et al 1993). Psa has been detected in kiwifruit pollen in Italy and New Zealand (Gallelli et al 2011;Vanneste et al 2011), and contaminated pollen has been implicated in the spread of the disease .…”
Section: Introductionmentioning
confidence: 99%
“…In 'Hayward', pollen is transferred through wind (Intoppa & Piazza 1990;Costa et al 1993;Vaissiere et al 1993) and insect foraging (PalmerJones & Clinch 1974;Clinch 1984;Goodwin 1987). Honey bee hives are introduced to almost all New Zealand orchards, but are not introduced to some Italian kiwifruit orchards, where large fans are used to blow pollen between plants (personal observation).…”
Section: Introductionmentioning
confidence: 99%